Kihívások és reformok a közszektorban - Mika, János; Turcsányi, Katalin (Jelenkori Társadalmi és Gazdasági Folyamatok, 2009)
Services form and content of Financial base function of the welfare state was increasing on the development countries still economic crises of ’70s was queried on the twentieth century by increasing change of economy of 60’s. Confiedence of political institution systems significantly decrease on the part of the development countries at same time. At 80’s reforms and development programs were entered on the public sector. Priority of private sector are advertised by programs on the first wave of reform programs and these programs was mainly typical, which has target. The target is a privatisation of the public sector. Further on these programs are complemented with outsourcing of public sector and more complex proposal of realignment of public sector. Programs got similar lines and technology (leadership, reorganization steps) and on the other trend of reform. Mainly question of reforms and equilibrum between public and private sector are reviewed by this study